Debit card usage and its impact among consumer in Malaysia / Rabiatul Adawiyah Mohd Khushaini - Mohd Khushaini, Rabiatul Adawiyah (2011)
Debit card use at the point of sale has grown dramatically in recent years in worldwide. However, many questions remain regarding patterns of debit card use, consumer preferences when using debit, and how consumer might respond to this card transaction. Malaysia needs a new approach, a new determination driven by the 1Malaysia spirit, to propel Malaysia into the next level of high growth. Policymakers should monitor the card payment industry to see if better coordinates security efforts, and if not, consider actions to help the industry overcome barriers to effective development of security